Magnitude and Determinants of Nurses’ Perceived Stress and Burnout in a Tertiary Eye Hospital - Shaibani, Wadha Al; Al-Qahtani, Maha; AlAmri, Enas; Khandekar, Rajiv (Archives of Clinical and Medical Case Reports, 2020)
Purpose: To assess the prevalence and determinants of stress among nurses of a tertiary eye hospital. Methods: This cross sectional survey was held in 2019. Nursing staff of our eye hospital provided feedback about ten possible causes of stress in their profession and ten effects of stress on mental health of nurses. Five graded Liker scale was used to generate stress score. It was graded as none, mild, moderate and severe and correlated to the determinants. Results: We surveyed 212 participants. Less than 4% of participants were Saudi nurses and 7% were male nurses. More than two thirds of nurses were in the profession for more than 10 years. The median stress score was -3.0 (IQR -9.0 ; +3.0) The stress was absent in 46 [21% (95% CI 16.1 ; 27.2)]. The stress was none in (46; 22%), mild (88; 22%), moderate (43; 20%) and severe (35; 16%). The occupation related stress was not associated significantly to gender (P = 0.5), nationality (P = 0.9) and rotation duties (P = 0.1). However it was more among nurses working in Inpatient units than other work station (P = 0.02). Overload of work, poor cooperation of eye patients, criticism of work, negligent coworkers and difficulty in interacting with eye doctors were leading causes of stress in more than two third of participating nurses. Conclusions: One in four nurses of tertiary eye hospital expressed severe grade of stress. Measures to reduce the stress could improve mental health of nurses and patient care.